Entre lo orgánico y lo inorgánico: la experiencia del hacerse cosa en Perniola y Braidotti - Pomposini, Antonio (2019)
The objective of this article is to explore the work of two contemporary authors: Mario Perniola and Rosi Braidotti. They both defend an immanent materialism in which they find that there can be no radical distinction between human beings and the matter that surrounds them. An appeal to transcendental reason is no longer possible for them if one wants to understand and describe contemporary society. Each author explains, from their viewpoint, how the notion of subjectivity has been transformed, what the importance of difference is and what the role of sensibility should be, exploring, thusly, the ways in which the human interacts and melds with the world of the inorganic in this posthuman context. This article presents the positions of both authors in order to explore the extent to which possible connections and agreements can be drawn, as well as their key differences.